Epilepsy Benchmarks Area II: Prevent Epilepsy and Its Progression. Issue 1 (January 2020) - Binder, Devin K.; Boison, Detlev; Eid, Tore; Frankel, Wayne N.; Mingorance, Ana; Smith, Bret N.; Dacks, Penny A.; Whittemore, Vicky; Poduri, Annapurna
Area II of the 2014 Epilepsy Research Benchmarks aims to establish goals for preventing the development and progression of epilepsy. In this review, we will highlight key advances in Area II since the last summary of research progress and opportunities was published in 2016. We also highlight areas of investigation that began to develop before 2016 and in which additional progress has been made more recently.